Diversity of endophytic fungi in cajuput leaf waste (Melaleuca cajuputi) - ANA WIDIANA; UKIT UKIT; AFIFAH THAHIRAH; EPA PAUJIAH (Society for Indonesian Biodiversity, 2019)
Abstract. Widiana A, Ukit, Thahirah A, Paijiah E. 2019. Diversity of endophytic fungi in cajuput leaf waste (Melaleuca cajuputi). Biodiversitas 20: 562-569. Cajuput Oil Factory at Jatimunggul, Indramayu of Forest Management Unit of Perum Perhutani (State Forest Enterprises) produces cajuput leaf waste during distillation process. This waste is difficult to decompose due to the presence of lignin in the secondary cell wall. Therefore, fungi are needed to produce some enzymes for speeding up the degrading process. This research was aimed at finding out the diversity of fungi growing in the cajuput (Melaleuca cajuputi Powell) leaf waste of zero, two and four months old. The result indicated that a total of 14 species of fungi belonging to four genera namely Aspergillus, Arthrinium, Rhizopus, and one unidentified genus are produced by cajuput leaf waste. Ten different types of endophytic fungi were isolated from two-month-old waste, seven Rhizopus and types of fungi were found in the zero-month-old waste, and only five types of isolates are found in the four-month-old waste. Three species of isolated fungi were also tested for their cellulase enzyme activity.